التدخل الدولي الإنساني كآلية لحماية حقوق الإنسان: أي مستقبل لمبدأ السيادة - جارد, محمد (University of Eloued جامعة الوادي, 2022)
لقد أصبح مفهوم التدخل الدولي الإنساني من أكثر المواضيع الشائكة التي تطرح جدلا كبيرا على الساحة الدولية لما يطرحه من إشكالات قانونية و تناقضات في مقابل مبدأ عدم التدخل و مبدأ السيادة ، فهو يحمل في بعض جوانبه اعتداء على هذين المبدأين المكرسين في المواثيق الدولية من جهة ، و من جهة أخرى فإنه يمثل حماية لحقوق الإنسان من التهديدات و الإنتهاكات الجسيمة التي قد تتخفى وراء فكرة السيادة و مبدأ عدم التدخل. و لهذا ، سنحاول من خلال هذه الدراسة تحديد طبيعة العلاقة و الرابطة بين المفاهيم الجديدة لفكرة السيادة و مبدأ عدم التدخل و بين فكرة التدخل الدولي الإنساني ، و ضبط حدود كل منهما ، بما يحقق التوازن بين هذه المفاهيم انسجاما مع الإهتمامات الكبرى للمجتمع الدولي في مجال حماية حقوق الإنسان. الكلمات المفتاحية: التدخل الدولي الإنساني ، فكرة السيادة ، مبدأ عدم التدخل ، حقوق الإنسان. Abstract : The concept of international humanitarian intervention has become one of the most thorny topics that pose a great controversy in the international arena because of its legal problems and contradictions as opposed to the principle of non-sovereignty, as it carries in some respects an attack on these principles enshrined convention on the one hand, and on the other hand it represents the protection of Human Rights from serious threats and violations that may hide behind the idea of sovereignty and the principle of non-interference. There fore , through this study, we will try to define the nature of the relationship between the new concepts of sovereignty and the principle of non-interference with the idea of humanitarian intervention, and to control the boundaries of each other, in order to balance these concepts in line with the great concerns of the international community in the field of the protection of Human Rights. Keywords: international humanitarian intervention, the idea of sovereignty, the principle of non-intervention, Human Rights.
International Humanitarian Intervention as a Mechanism for H uman Rights Protection What Future Has the Principle of Sovereignty?
مقال
Keywords: التدخل الدولي الإنساني ، فكرة السيادة ، مبدأ عدم التدخل ، حقوق الإنسان.; International humanitarian intervention; the idea of sovereignty; the principle of non-intervention; Human Rights.